Straße in die Vergangenheit - Torau, Cord; Lounsbach, Brian (Sellier, 1985)
Time-traveling Petra visits her neighborhood at intervals over th past 1000 years.
Keywords: Geschichte; Deutschland; Germany -- History -- Juvenile fiction